Short Horizon Return Predictability di Pasar Modal Indonesia - Erman Denny Arfianto; Ivan Irawan (Jurnal Pasar Modal dan Bisnis, 2019)
Purpose- This study aims to examine the effect of effective spread, price impact, trading volume, stock prices, and volatility of returns on the predictability of short-term returns (short horizon return predictability). Methods- This research offers a new approach perspective which is a market microstructure with intraday data to measure short horizon return predictability as an efficient market inversion. The sample in this study was 64 non-financial companies listed on the KOMPAS100 Index during October 2017-March 2018. Intraday data used using the 5-minute frequency obtained from Bloomberg. This study uses multiple linear regression analysis. Finding- This study found that price impact, trading volume, stock prices, and volatility have a positive impact on the predictability of long-term returns. This study also found that effective spread does not have a significant impact on the predictability of short-term returns.